Turkey's First Devaluation: 7 September 1946 Decisions - (:unkn) unknown (Peter Lang AG, 2019)
Turkey's first devaluation of 7th September Decisions is one of the most important economic events in the Turkish economic history in 1946. Turkey's foreign trade partners were defeated in the Second World War (WW2). Therefore, her foreign trade opportunities in the postwar period had narrowed. After WW2, the new order began to be established, pioneered by the United States, and in order to participate in this order, Turkey needed to make a number of changes. In this study, Turkey's first devaluation of 7th September Decisions will be examined, with a focus on state' expectations from the decision and the practical consequences of the devaluation. The Republican Archives, Parliamentary Papers, Resmi Gazete and Cumhuriyet and Ulus newspapers, which were published in September 1946, are used. © 2019 Peter Lang GmbH.
Keywords: Devaluation; Monetary Crisis; Ration 1946; Turkey